Optimal. Leaf size=32 \[ \left (e^3+x\right )^2-\log \left (2 x-e^6 x-x^2+\frac {\log (2)}{x}\right ) \]
________________________________________________________________________________________
Rubi [A] time = 0.48, antiderivative size = 35, normalized size of antiderivative = 1.09, number of steps used = 5, number of rules used = 4, integrand size = 99, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.040, Rules used = {6, 1594, 6742, 1587} \begin {gather*} x^2-\log \left (x^3-\left (2-e^6\right ) x^2-\log (2)\right )+2 e^3 x+\log (x) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 6
Rule 1587
Rule 1594
Rule 6742
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {-2 x^2+2 x^3+4 x^4-2 x^5+e^3 \left (4 x^3-2 x^4\right )+e^6 \left (x^2-2 e^3 x^3-2 x^4\right )+\left (1+2 e^3 x+2 x^2\right ) \log (2)}{\left (2-e^6\right ) x^3-x^4+x \log (2)} \, dx\\ &=\int \frac {-2 x^2+2 x^3+4 x^4-2 x^5+e^3 \left (4 x^3-2 x^4\right )+e^6 \left (x^2-2 e^3 x^3-2 x^4\right )+\left (1+2 e^3 x+2 x^2\right ) \log (2)}{x \left (\left (2-e^6\right ) x^2-x^3+\log (2)\right )} \, dx\\ &=\int \left (2 e^3+\frac {1}{x}+2 x+\frac {x \left (-4+2 e^6+3 x\right )}{\left (2-e^6\right ) x^2-x^3+\log (2)}\right ) \, dx\\ &=2 e^3 x+x^2+\log (x)+\int \frac {x \left (-4+2 e^6+3 x\right )}{\left (2-e^6\right ) x^2-x^3+\log (2)} \, dx\\ &=2 e^3 x+x^2+\log (x)-\log \left (-\left (\left (2-e^6\right ) x^2\right )+x^3-\log (2)\right )\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [C] time = 0.11, size = 48, normalized size = 1.50 \begin {gather*} x \left (2 e^3+x\right )+\log (x)-\text {RootSum}\left [\log (2)+2 \text {$\#$1}^2-e^6 \text {$\#$1}^2-\text {$\#$1}^3\&,\log (x-\text {$\#$1})\&\right ] \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.72, size = 33, normalized size = 1.03 \begin {gather*} x^{2} + 2 \, x e^{3} - \log \left (x^{3} + x^{2} e^{6} - 2 \, x^{2} - \log \relax (2)\right ) + \log \relax (x) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.17, size = 35, normalized size = 1.09 \begin {gather*} x^{2} + 2 \, x e^{3} - \log \left ({\left | x^{3} + x^{2} e^{6} - 2 \, x^{2} - \log \relax (2) \right |}\right ) + \log \left ({\left | x \right |}\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.09, size = 31, normalized size = 0.97
method | result | size |
risch | \(2 x \,{\mathrm e}^{3}+x^{2}+\ln \relax (x )-\ln \left (x^{3}+\left ({\mathrm e}^{6}-2\right ) x^{2}-\ln \relax (2)\right )\) | \(31\) |
default | \(x^{2}+2 x \,{\mathrm e}^{3}+\ln \relax (x )-\ln \left (x^{2} {\mathrm e}^{6}+x^{3}-2 x^{2}-\ln \relax (2)\right )\) | \(34\) |
norman | \(x^{2}+2 x \,{\mathrm e}^{3}-\ln \left (-x^{2} {\mathrm e}^{6}-x^{3}+2 x^{2}+\ln \relax (2)\right )+\ln \relax (x )\) | \(35\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.39, size = 30, normalized size = 0.94 \begin {gather*} x^{2} + 2 \, x e^{3} - \log \left (x^{3} + x^{2} {\left (e^{6} - 2\right )} - \log \relax (2)\right ) + \log \relax (x) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 5.41, size = 33, normalized size = 1.03 \begin {gather*} \ln \relax (x)-\ln \left (x^2\,{\mathrm {e}}^6-\ln \relax (2)-2\,x^2+x^3\right )+2\,x\,{\mathrm {e}}^3+x^2 \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 1.15, size = 29, normalized size = 0.91 \begin {gather*} x^{2} + 2 x e^{3} + \log {\relax (x )} - \log {\left (x^{3} + x^{2} \left (-2 + e^{6}\right ) - \log {\relax (2 )} \right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________